PENERAPAN HAK EX OFFICIO HAKIM TERHADAP PERKARA CERAI TALAK - A. Uswatun Hasanah Aswar; Supardin; Siti Nurul Fatimah (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
This study discusses the application of ex officio rights of judges to divorce cases at the Bulukumba Religious Court Class II. The judge at the Bulukumba Religious Court Class II once exercised his ex officio rights which ordered the applicant (husband) to hand over the iddah and mut'ah income to the respondent (wife) even though the respondent or the wife did not file a counterclaim. Therefore, it is necessary to explore how the ex officio rights of judges are applied at the Bulukumba Religious Court and the legal consequences of implementing these ex officio rights. This type of research is an empirical legal research that is a study with field data as the main data source, such as the results of interviews and observations. The results of this study indicate that in the Bulukumba Religious Court, judges exercise their ex officio rights, for example in Decision Number 799/Pdt.G/2021/PA.Blk and Decision Number 574/Pdt.G/2021/PA.Blk and one of the considerations is to provide justice for a wife who will be divorced by her husband. However, the application of this ex officio right is rarely used because most divorce cases at the Bulukumba Religious Court are decided verstek, making it difficult for the judge to prove that the applicant is entitled to receive the right or not. The legal consequence of applying the ex officio rights of judges is to realize the principle of justice by putting everything in its share. In other words everyone fulfills their responsibilities and receives what is due to them. Keywords: Divorce, Judge Ex Officio Rights, Religious Courts